2010
DOI: 10.1517/14712598.2010.512914
|View full text |Cite
|
Sign up to set email alerts
|

The role of talactoferrin alfa in the treatment of non-small cell lung cancer

Abstract: The current role of Talactoferrin alpha in the treatment of NSCLC is described and we explore potential future roles for this drug in both early stage and advanced stage disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…These findings have limited both the systemic use and therapeutic potential of first generation ACPs, and presently the only major candidate in this class of peptides with promise for medical use is the neutraceutical protein, lactoferrin (Table ), which has been patented as an anticancer agent . In previous human clinical trials, orally administered lactoferrin was shown to reduce the risk of colon carcinogenesis, and currently the protein is in an advanced human clinical trials as an orally administered treatment for nonsmall lung cell cancer (Table ) . The strategy adopted by most efforts to design a therapeutically useful second generation ACPs seems to be primarily focused on optimizing the structural and physiochemical parameters of these peptides for this use .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings have limited both the systemic use and therapeutic potential of first generation ACPs, and presently the only major candidate in this class of peptides with promise for medical use is the neutraceutical protein, lactoferrin (Table ), which has been patented as an anticancer agent . In previous human clinical trials, orally administered lactoferrin was shown to reduce the risk of colon carcinogenesis, and currently the protein is in an advanced human clinical trials as an orally administered treatment for nonsmall lung cell cancer (Table ) . The strategy adopted by most efforts to design a therapeutically useful second generation ACPs seems to be primarily focused on optimizing the structural and physiochemical parameters of these peptides for this use .…”
Section: Discussionmentioning
confidence: 99%
“…316 In previous human clinical trials, orally administered lactoferrin was shown to reduce the risk of colon carcinogenesis, 317 and currently the protein is in an advanced human clinical trials as an orally administered treatment for nonsmall lung cell cancer (Table III). [318][319][320] The strategy adopted by most efforts to design a therapeutically useful second generation ACPs seems to be primarily focused on optimizing the structural and physiochemical parameters of these peptides for this use. [321][322][323] Based on the findings of this review, we suggest that the most efficient strategies for the design of therapeutically useful ACPs will be those which take into account the characteristics of not only these peptides, but also those of their target cancer cell membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Through the induction of IFN‐γ secretion and the activation of CD8 + T and NKT cells, oral TLF inhibits ERBB2‐driven mammary carcinogenesis in transgenic mice and the growth of transplantable tumors (15). TLF has also been (1618) and is currently being investigated (19) as a therapeutic anticancer agent in clinical trials.…”
mentioning
confidence: 99%
“…Use of recombinant lactoferrin offers new therapeutic possibilities for treating bacterial and viral infections (144147). …”
Section: Future Directionsmentioning
confidence: 99%